Mensurando a corrente elétrica em jatos relativísticos - Oliveira, Aleandro dos Santos (Universidade Federal Rural do Semi-Árido, 2018)
In this paper is done the study of the constituent parts for the formation of relativistic jets so that from a mining of articles necessary data collection was done to measure the electric current of jets astrophysicists in two sources, 3C 273 and Messier 87, using the method applied by Kronberg (2011) and also make the comparison of the value measured with the mass of the black hole looking for a relationship, since the black hole is fundamental for the formation of jets at Kiloparsec (Kpc). With the unprecedented use of a virtual telescope with a diameter greater than that of Earth made in 2018, it is possible to observe more details of the astrophysical jets, with observations it will be possible to better understand these structures and obtain information necessary to measure the electric current of these jets.
Monografia
Keywords: Jatos relativísticos; Corrente elétrica; Jatos astrofísicos; Buracos negros; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA